Nutritional and nutraceutical components of four Cantharellus species (Cantharellaceae, Cantharellales) from the Mountain Region, Veracruz, Mexico - Hernández Marañón, Edgar Josúe; Andrade-Torres, Antonio; Chen, Jie; Núñez-Pastrana, Rosalía; Pérez-Moreno, Jesús; Hernández-Marañón, Anahí; Llarena-Hernández , Régulo Carlos (Instituto de Ecología, A.C., 2023)
Background and Aims: Cantharellus species are traded in agricultural markets of the Mountain Region, Veracruz, Mexico, as an appreciated mushroom. The objective of this study was to analyze nutrients and nutraceutical properties in four Cantharellus species from Veracruz: antioxidant activity, total phenols, flavonoids, ascorbic acid, lycopene, and β-carotene; as well as the nutritional properties: dry matter, total ashes, crude protein, crude fat, crude fiber, moisture, carbohydrates and energy value of four wild edible mushrooms (Cantharellus violaceovinosus, C. veraecrucis, C. roseocanus and Cantharellus sp.). Methods: Basidiomas of Cantharellus spp. were collected in the Mountain Region, Veracruz, Mexico. The ITS and tef-1α regions were amplified and sequenced. Species were identified molecularly based on the BLAST results. Samples were lyophilized and stored at 4 °C in vacuum bags for the preservation of nutraceutical and nutritional compounds. A methanol-water mixture (80:20 v/v) was used to extract the nutraceutical compounds and to analyze them by spectrophotometric techniques. Key results: In general, outstanding values ​​were found in C. violaceovinosus both in crude protein content (8.04 g/100 g-1) and in antioxidant capacity 2.28 mg TE/g extract. For flavonoids, C. roseocanus showed 2.98 mg QE/g extract and 6.23±0.68 mg/g of carotene. In addition, a high energy value was found in C. violaceovinosus (266.53 Kcal/100g) and C. roseocanus (222.73±15.43 Kcal/100 g). The nutritional and nutraceutical content of C. violaceovinosus, C. veraecrucis and C. roseocanus is presented for the first time. Conclusions: The results show these species from nutritional and nutraceutical perspectives. Cantharellus violaceovinosus showed the highest values of the parameters evaluated. The consumption of these species constitutes an alternative source of protein and nutraceutical components that contribute to food security.